2020
DOI: 10.1021/acsabm.0c00170
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin Quantification in Human Blood Serum by Deoxygenation Reaction Switch-Triggered Fluorescent Probe

Abstract: A coumarin-based fluorescent compound, bilirubin fluorescent probe N-oxide (BFPNox), was successfully designed and synthesized for highly selective and sensitive detection of free bilirubin with short response time. The fluorescence "turn-on" response of the probe is based on the in situ generated Fe 2+mediated deoxygenation reaction of N-oxide from the diethylarylamine group of the probe, where the group attached to the coumarin π-conjugated system is responsible for the fluorescence quenching state of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Moreover, BR is detected through spiking methods and does not represent a clinical detection. In the case of "Turn ON" fluorescent organic molecular systems 16,17 (Table S3, † ref.…”
Section: Analysis Of Bilirubin In Clinical Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, BR is detected through spiking methods and does not represent a clinical detection. In the case of "Turn ON" fluorescent organic molecular systems 16,17 (Table S3, † ref.…”
Section: Analysis Of Bilirubin In Clinical Samplesmentioning
confidence: 99%
“…Recently reported coumarin-based N -oxide–Fe 3+ mixtures have revealed “Turn ON” fluorescence in the presence of bilirubin owing to the deoxygenation process by the in situ generated Fe 2+ (ref. 16 and 17) and have been tested and even used for the detection of bilirubin from human serum. In another approach, in non-fluorescent resorcinol-sucrose CDs and Cu 2+ complex, the competitive binding of Cu 2+ with bilirubin released the fluorescence of the CDs.…”
Section: Introductionmentioning
confidence: 99%
“…Bilirubin (BR) is a neurotoxic, yellow-orange degradation product of heme catabolism whose turnover is greatly associated with jaundice. , Under a typical physiological state, BR is enzymatically converted to mono- and di-glucuronide conjugates in the liver and gets rid of the body along with the body fluids . The human serum contains <25 μM (<1.2 mg/dL) BR, which increases up to 50 μM during the jaundice condition. , Such a medical condition is fatal as it can accumulate in body organs; thereby, its toxicity leads to mental disorder, hepatitis, Gilbert syndrome, brain damage, anemia, and even death to neonatals due to the inhibition of mitochondrial functions. Several reports have found that a low serum BR level is also connected with several diseases like coronary artery disease and atherosclerosis. , Thus, monitoring the abnormal concentration of BR, a key biomarker for various physiological processes in our body, precisely and early in low concentrations is of immense importance to ensure early treatment.…”
Section: Introductionmentioning
confidence: 99%
“…3 The human serum contains <25 μM (<1.2 mg/dL) BR, which increases up to 50 μM during the jaundice condition. 4,5 Such a medical condition is fatal as it can accumulate in body organs; thereby, its toxicity leads to mental disorder, hepatitis, Gilbert syndrome, brain damage, anemia, and even death to neonatals due to the inhibition of mitochondrial functions. 6−11 Several reports have found that a low serum BR level is also connected with several diseases like coronary artery disease and atherosclerosis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The fluorescence method detected purification bilirubin has a high linear correlation, but the detection method is dependent on chemical reactions. In addition, for biological samples with a complex composition, such as urine and blood, the anti-interference and linear correlation of fluorescence-based methods do not reach the expected level of accuracy [ 38 40 ]. Besides the methods above, the excess bilirubin in the blood will lead to the skin becoming yellow, and then, the method using diffuse reflectance spectroscopy to quantify bilirubin from skin reflectance spectra has been proposed [ 41 ].…”
Section: Introductionmentioning
confidence: 99%